Comparative analysis of solar panel output power with variations of Heatsink type cooling systems - Dwi Yulia Handayani; James Julian; Fitri Wahyuni; Ridwan Daris Naufal (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering))
The heatsink is installed on the back sheet of the solar panel in the form of a fin so that the air under the solar module helps the heatsink perform cooling. Temperature testing uses a thermocouple temperature sensor at several calibrated points, taking volt and current data using a multimeter. The results of this test obtained a deviation comparison value between solar panels without a heat sink and using a heat sink of ±1%. So, the similarity of deviation values from the research is used as a control variable. From all the data that has been taken, using heat sinks on solar panels can reduce excess heat in the solar panel modules. The heat transfer that occurs in this experiment is by conduction and convection. The heatsink's good performance in releasing heat with high power output can be seen at 12.25 because the resulting thermal efficiency is related to the power released at the same time. The thermal efficiency value is 20.88%, and the power increase is 19.31%.